2019
DOI: 10.1002/smi.2909
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French version of the Forms of Self‐Criticizing/Attacking and Self‐Reassuring Scale

Abstract: Background: Self-criticism and self-reassurance are internal processes of self-to-self relating that have received increasing attention in psychology. The Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS), which was first studied by Gilbert, Clarke, Hempel, Miles, and Irons, is a self-report instrument that has been used in various populations and has shown satisfactory reliability. The goal of this work is to explore the psychometric properties of a French version of the scale in a large n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Our results indicate a clear relationship between SC facets and negative psychological health. These correlation patterns are consistent with previous findings regarding IS and HS factors, which have been associated with high levels of depression, anxiety, stress, pessimism, isolation, shame, eating-related difficulties, body mass index, and facial-emotion recognition difficulties [ 44 , 48 , 72 75 ]. Along these lines, RS has been associated with high levels of self-compassion [ 76 ], dispositional optimism [ 44 ], weight-related positive affect, and overall mental well-being [ 77 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results indicate a clear relationship between SC facets and negative psychological health. These correlation patterns are consistent with previous findings regarding IS and HS factors, which have been associated with high levels of depression, anxiety, stress, pessimism, isolation, shame, eating-related difficulties, body mass index, and facial-emotion recognition difficulties [ 44 , 48 , 72 75 ]. Along these lines, RS has been associated with high levels of self-compassion [ 76 ], dispositional optimism [ 44 ], weight-related positive affect, and overall mental well-being [ 77 ].…”
Section: Discussionsupporting
confidence: 92%
“…This result supports the previous findings of Sommers-Spijkerman et al [ 52 ] regarding the three-factor solution and rationale of the cognitive-evolutionary model [ 68 ]. In addition, the three-dimensional model provides a better fit than the unidimensional and bifactorial ones according to the results of the confirmatory factor analyses of the FSCRS in clinical and non-clinical samples [ 44 , 45 , 48 , 69 71 ]. This is in contrast with a large intercultural study which has shown that a two-factor model of RS and SC (combining IS and HS) had a superior fit, although the three-factor one was acceptable too [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores indicate a greater capacity for self-compassionate responding to oneself in times of adversity. Moderate to strong associations have been observed between the FSCRS Reassured Self scale and other measures of self-compassion (Castilho et al, 2015;Hermanto & Zuroff, 2016;Leboeuf et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The Inadequate self (IS) and Hated self (HS) subscales of “The Forms of Self-Criticizing/Attacking and Self-Reassuring Scale” (FSCRS; Gilbert et al, 2004 ) were used to assess sexual minorities’ self-criticism in the past year. The IS subscale has 9 items (e.g., I remember and dwell on my failings ), focusing on self-criticism caused by caring about inadequacies; the HS subscale has 5 items (e.g., I do not like being me ), focusing on self-criticism caused by self-loathing (Leboeuf et al, 2020 ). Each item was rated on a 5-point scale, ranging from 1 ( not at all like me ) to 5 ( extremely like me ).…”
Section: Methodsmentioning
confidence: 99%